Measurement for Management DecisionMeasurement for Management Decision, by MasonRichard O. and SwansonE. Burton. Reading, Mass.: Addison-Wesley, 1981, 500 pp., $22.75 (cloth). - Sooklal, Lessey (Academy of Management Review, 1982)
The article reviews the book ?Measurement for Management Decision,? by Richard O. Mason and E. Burton Swanson.